Pembangunan Pembangkit Listrik Tenaga Air Tampur-I Terkait dengan Emisi Gas Rumah Kaca dan Putusan Pengadilan Tata Usaha Negara Banda Aceh Nomor 7/G/Lh/2019/PTUN.BNA - Moch. Daffa Syahrizal (Jurnal Hukum Lex Generalis, 2021)
The Hydroelectric power plant is presented with scientific developments that determine that hydropower is a source of Greenhouse Gas (GHG) emissions. WALHI sued the IPPKH which was issued for the construction of the Tampur-I hydroelectric power plant. Based on research with a normative juridical approach, hydropower as a source of GHG has not been inventoried, so its existence in Baku Mutu Emisi and in the AMDAL is not found. Then against WALHI's lawsuit, the decision of the Banda Aceh State administrative court No.7/G/LH/2019/PTUN.BNA which is in accordance with the law is able to become a forest protector in Aceh when the licensing&AMDAL instrument failed.